2022
DOI: 10.3390/antibiotics11060796
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Ivermectin for the Prevention and Treatment of COVID-19: A Double-Blinded Randomized Placebo-Controlled Study

Abstract: The safety and efficacy of ivermectin for the prevention and treatment of COVID-19 are still controversial topics. From August to November 2021, we conducted a double-blinded, randomized controlled trial at Siriraj Hospital, Thailand. Eligible participants were adults ≥ 18 years with suspected COVID-19 who underwent a SARS-CoV-2 RT-PCR test. After enrollment, the participants were randomized to receive either ivermectin (400–600 µg/kg/d) or placebo once daily for 3 days. Among 983 participants, 536 (54.5%) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The characteristics of these 8 studies are presented in Table 1. [26][27][28][29][30][31][32][33] The study period of the included studies was from May 2020 to December 2021; the studies involved 165 866 participants. The COVID-19 incidence in these studies ranged from 5.2% to 73.3%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of these 8 studies are presented in Table 1. [26][27][28][29][30][31][32][33] The study period of the included studies was from May 2020 to December 2021; the studies involved 165 866 participants. The COVID-19 incidence in these studies ranged from 5.2% to 73.3%.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes the risk of bias for both randomized and cohort studies included in this review. [26][27][28][29][30][31][32][33] Overall, the included studies had moderate to high risks of bias. Cohen's kappa coefficient was excellent (0.83).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also revealed the antiviral activity of ivermectin associated with the ability to inhibit flavivirus replication by targeting the NS3 helicase [ 61 ], block the importin alpha/beta-mediated nuclear transport of viral proteins, capable of inhibiting the replication of HIV-1 and dengue virus [ 62 ], and inhibit SARS-CoV-2 replication in vitro [ 63 ]. Currently, the possibility of using ivermectin for the prevention and treatment of inflammatory processes induced by viral diseases [ 8 , 9 , 10 , 11 , 12 , 13 ], as well as for the treatment of cancer patients [ 14 ], is being studied. We assumed that the therapeutic effect of ivermectin is associated not only with antiviral activity, but also with its effect on human innate immunity, namely, with its effect on neutrophil function.…”
Section: Discussionmentioning
confidence: 99%
“…Some case series analysis demonstrates the ability of ivermectin to alleviate disease-associated severity and recovery rate [ 10 , 11 ]. Another analysis failed to demonstrate the efficacy of ivermectin in the treatment of COVID-19 [ 12 , 13 ]. The therapeutic effect of ivermectin is highly dependent on the phase of the disease in which the patient receives the drug [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A double-blinded, randomized controlled trial was conducted in Thailand in 983 adults aged > 18 years with suspected COVID-19. The efficacy of a 3-day once daily dose (400–600 μg/kg/day) of ivermectin for the prevention and treatment of COVID-19 in confirmed PCR-positive cases [ 28 ]. This ivermectin should not be used for either prevention or treatment of COVID-19 in populations with a high rate of COVID-19 vaccination.…”
mentioning
confidence: 99%